2020
DOI: 10.1136/ijgc-2019-000991
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative glycemic measures among non-fasting gynecologic oncology patients receiving carbohydrate loading in an enhanced recovery after surgery (ERAS) protocol

Abstract: IntroductionPreoperative carbohydrate loading is an effective method to control postoperative insulin resistance. However, data are limited concerning the effects of carbohydrate loading on preoperative hyperglycemia and possible impacts on complication rates.MethodsA prospective cohort study was performed of patients enrolled in an enhanced recovery after surgery pathway at a single institution. All patients underwent laparotomy for known or suspected gynecologic malignancies. Patients who had been diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…Overall, preoperative carbohydrate loading has been shown to be an effective method to control postoperative insulin resistance [ 30 , 31 ]. However, data are limited concerning the effects of carbohydrate loading on preoperative hyperglycemia and insulin management in patients with ovarian cancer patients previous to interval cytoreductive surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, preoperative carbohydrate loading has been shown to be an effective method to control postoperative insulin resistance [ 30 , 31 ]. However, data are limited concerning the effects of carbohydrate loading on preoperative hyperglycemia and insulin management in patients with ovarian cancer patients previous to interval cytoreductive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative carbohydrate loading in our prehabilitation group was not associated with intraoperative increased risk of hyperglycemia, postoperative insulin requirement neither intraoperative nor postoperative complications. Similarly, Alimena et al reported that carbohydrate loading was associated with an increase in preoperative glucose values without impacting the complication rates [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fast-track surgery (FTS), also known as Enhanced Recovery After Surgery (ERAS), refers to the combination of optimization measures for perioperative treatment with evidence-based medical evidence, and the adoption of an optimized clinical path through multidisciplinary teamwork, in order to reduce the physical and psychological trauma stress of surgical patients, reduce complications and shorten hospital stays, and accelerate the recovery of patients [11]; FTS was first advocated by Danish physician Kehlet [12,13], and has been widely used in countries around the world [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…El tipo de cirugía en los valores de glicemia intraoperatoria con un incremento significativo (p< 0.05) en la cirugía abierta versus laparoscópica (87 mg/dl ± 7 vs 85 mg/dl ± 7) y no influye en los niveles de glicemia pre y posoperatoria (p> 0.05), así lo demuestran Khalimonchyk y Klygunenko en Ucrania durante el 2019 en su estudio determinan que los pacientes sometidos a técnica laparoscópica no muestran un incremento significativo de los niveles de glicemia intraoperatoria en relación con los valores preoperatorios, por su parte, Alimena y cols., muestran que las pacientes sometidas a cirugía abierta (laparotomía) incrementan sus niveles de glicemia intraoperatoria en comparación con los basales (27,28).…”
Section: Glicemia Perioperatoria (Mediana Mg/dl)unclassified